Voltammetric Reduction Behavior and Electrode Kinetics - Balaji,K. (2011)
The electrochemical reduction behavior of cefepime and cefpirome has been studied using cyclic voltammetry in Britton Robinson (BR) buffer ranging from pH 2.0 to 12.0. Cefepime and cefpirome are found to give two well defined peaks and these peaks are attributed to the reduction of the azomethine group (>C=N-) by two electron process in two steps. Kinetic parameters such as diffusion coefficient (D) and forward rate constant (Kºf,h) values are evaluated and a reduction mechanism is proposed. The result indicates that the process of both the compounds is irreversible and diffusion controlled. A simple and rapid differential pulse polarographic method has been developed for the determination of cefepime and cefpirome in pharmaceutical formulations and spiked urine samples using the standard addition method. The lower detection limits are found to be 4.6×10-8 mol. L-1 and 8.52×10-8 mol. L-1 for cefepime and cefpirome, respectively.